ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT BERWAKAF TUNAI SEPERTI YANG DIJELASKAN TEORI PLANNED BEHAVIOR - Pamungkas, Ryan; Fitianto, Bahtiar (Islamic Economics and finance in Focus, 2022)
Income redistribution has become an important issue in Indonesia. In this regard, Islam has several instruments to address the problem; one of which is waqf. This type of endowment has developed much. Along the course of time, cash waqf has been implemented. As this waqf should be highly potential, this research aims to identify people’s intention to make this charity using Theory of Planned Behavior. Here income and service quality were used as the variable, while quantitative analysis and multiple linear regression served as the research method. This study finds that income has a significant effect on people’s intention to make cash waqf and that service quality does not significantly influence the said intention.